Formulation of Fish Egg Snacks Substituting Tuna (Euthynnus affinis) Protein Concentrate: Sensory, Proximate, and Amino Acid Characteristics - Stephani Nesya Renamastika; Firda Agustin; Huda Oktafa; Rusdiarti; Kurniawan Erman Wicaksono (Indonesian Journal Publisher, 2026)
Background: Tuna is a fish known for its high protein content and is widely consumed by the community. “Fish egg snacks” are popular among people from diverse backgrounds. Purpose: This study was to determine the acceptability, nutritional content, and amino acid profile of “fish egg snack” formulations with tuna protein concentrate substitution. Methods: This study used an experimental design. The subjects used in the organoleptic testing were 25 semi-trained panelists. The stages of this study included the production of tuna protein concentrate and the production of fish egg snack. The analyses conducted included organoleptic analysis, nutritional content analysis, and amino acid profile analysis. The data were analyzed descriptively. Results: F4 was the best formula based on the De Garmo assessment of organoleptic testing and protein content. F4 was found to have a total energy of 496.86 kcal, ash content of 2.35%, moisture content of 2.51%, carbohydrates of 50.97%, and total fat content of 23.26%. In addition, the most abundant amino acid found in F4 was L-glutamic acid. Conclusion: F4 is the best fish egg snack formulation, and L-glutamic acid is the most abundant amino acid found in F4.